Environmental and Management Risk Factors for Goat Mastitis in Banyuwangi - Dewi Sri Lestari; Boedi Setiawan; Amung Logam Saputro; Maslichah Mafruchati; Ratih Novita Praja; Ragil Angga Prastiya (Journal of Basic Medical Veterinary, 2025)
Mastitis is a persistent and economically significant health problem in dairy goats in Banyuwangi, East Java, where smallholder production systems dominate. This review synthesises current evidence on the primary risk factors contributing to the high prevalence of subclinical mastitis in the region. Local studies consistently report Staphylococcus aureus as the leading etiological agent, frequently exhibiting antimicrobial resistance linked to unsupervised antibiotic use. Host-related factors such as advanced parity, udder lesions, and teat-end damage increase susceptibility to intramammary infection. Management practices—including inadequate milking hygiene, use of shared towels, absence of pre- and post-dipping, and irregular equipment sanitation—facilitate the transmission of contagious pathogens. Environmental conditions, particularly high humidity and poor housing sanitation, further elevate infection pressure. Socio-economic constraints and limited farmer knowledge about subclinical mastitis and antibiotic stewardship exacerbate disease persistence. The multifactorial nature of mastitis in Banyuwangi underscores the need for context-appropriate interventions combining improved hygiene practices, better housing management, routine screening, and responsible antimicrobial use. Strengthened farmer education and targeted surveillance are essential to reduce mastitis prevalence and enhance the sustainability of goat dairy production in the region.